Hubungan Kecerdasan Emosional Terhadap Tingkat Stres Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa Di Masa Pandemi COVID-19 - Ni Luh Gede Taman Kristanti; Putu Nita Cahyawati; I Gde Yudhi Kurniawan (Aesculapius Medical Journal, 2022)
The COVID-19 pandemic has had a major impact on various sectors of life, including the world of education in Indonesia Online learning is one of the developments that occur in the field of education. This condition can affect the stress level of students. Previous studies have reported that there is a link between emotional intelligence and stress. The purpose of this study was to determine the relationship between emotional intelligence and stress levels of students from the Faculty of Medicine and Health Sciences, Warmadewa University during the COVID-19 pandemic. This research is an analytic study with a cross sectional design. The sample of this study were 106 students of the Faculty of Medicine and Health Sciences, Warmadewa University. This survey revealed, out of 106 respondents, 67.9% had high emotional intelligence and 32.1% students with low emotional level. Analysis of stress levels obtained 59.4% of students classified as normal and 40.6% classified as stressed. Statistical analysis shows that there is a relationship between emotional intelligence and stress levels with a p value <0.05 and an OR of 2.675. These results indicate that respondents who have low emotional intelligence are 2 times more likely to experience stress than respondents who have high emotional intelligence.